Analysis of Land Cover Change 2015-2023 in Bima Regency Using Google Earth Engine - Ismi Asmawati; Ika Wulandari; Nisa Ul Istiqomah; Nuzla Af'idatur Robbaniyyah; Kurnia Ulfa; Muhammad Rijal Alfian (Jurnal Sains Natural, 2026)
Land cultivation is one of the activities related to land conversion, this conversion is an activity to change part or all of the land function into other functions. Bima Regency is one of the areas that has experienced land cover change. The research aims to analyze land cover in Bima Regency using Landsat Centinel-2A on the GEE platform. GEE is an alternative to image processing because it allows users to access and analyze large amounts of geospatial data with high efficiency. Land area data is obtained on the platform using the NDVI method, then the accuracy test with the help of the Python programming language, the accuracy results for land cover 2015-2016, 2016-2017, 2017-2018, 2018-2019, 2019-2020, 2020-2021, 2021-2022, 2022-2023 Overall accuracy are 9.73%, 34.12%, 14.61%, 10.77%, 4.95%, 12.72%, 72.5%, 0.06% respectively. Based on the results of the study, land cover change in Bima District did not occur significantly, where there was a change in land cover below 25% in 2015 to 2023, except in 2016-2017 and 2021-2022. The low accuracy value indicates the limitations of simple NDVI-based classification methods in detecting detailed land cover changes. Therefore, the results of this study need to be understood in the context of the limitations of the method and can be used as a basis for developing more complex methods in future studies.